Cold gas dynamic spraying of titanium coatings - Price, Timothy Simon (2008)
Cold gas dynamic spraying, CGDS, is a relatively new technique used to deposit materials onto the surface of a substrate. It differs to the majority of other thermal spray techniques as the substrate and particles are not exposed to high temperatures during the spraying process. This makes CGDS particularly advantageous for spraying materials such as titanium which react at high temperature. The aim of this project was to investigate the potential use of titanium coatings by CGDS as a surface treatment for medical prostheses. Titanium powder was deposited onto Ti6A14V substrate using helium gas at room temperature. Titanium coatings were also produced by a competing spray technique, shrouded arc spraying, to allow for a comparison of the two techniques to be made. Mechanical properties of the titanium coatings were measured and the influence of subsequent heat treating on the mechanical properties was also investigated. The coatings were characterised by investigating properties such as their bond strength, residual stress and stiffness, as well as the influence of the cold spray titanium coating on the fatigue life of a sprayed substrate. Scanning electron microscopy and optical microscopy techniques were also used to characterise the deposits. To further develop and optimise the CGDS process aluminium and copper coatings were also deposited and their mechanical properties compared to that of the titanium deposits. Additionally particle image velocimetry, PIV, was used to improve general understanding of the cold spray process and the effect that spray parameters have on the particle impact velocity.